The Artist: Silent Technique in Film Form - Agustinus Dwi Nugroho (Graduate School of Institut Seni Indonesia Yogyakarta, 2016)
The Artist is a film that uses the silent era techniques to visualize the film. This study sought to uncover what the motivation behind the use of techniques to the silent era films with his observation of the text of both aspects of the narrative as well as aspects of the technique. The findings of the observation process could be the basis of analysis. The Artist makes this silent era technology into a cinematic technique to visualize the film. This has become a strong motivation and able to demonstrate the strength of the story as a whole that tells about the silent era transition process from the perspective of the player. The silent era techniques were used to make this technique as a force in the film. This study focuses on how the technique of the silent era emerged as a new technique in the world of film and brings new perspective in film studies. This new technique emerged because it was never used fully in the present.